Integrated nursing and medical management improves outcomes in pediatric lobar pneumonia: a randomized controlled study - Hu, Yuxiao; Guo, Qianli; Liu, Xuejiao; Lv, Wenshan; Liu, Linlin (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the effectiveness of integrated nursing and medical management in children with lobar pneumonia, focusing on symptom relief, pulmonary function recovery, inflammation control, length of hospital stay, and caregiver satisfaction.MethodsFifty pediatric patients with lobar pneumonia were randomly assigned to receive either routine nursing care or an integrated medical and nursing intervention. Key clinical outcomes—including the duration of symptoms, pulmonary function indices, inflammatory markers, length of hospital stay, treatment efficacy, caregiver satisfaction, and adverse events—were compared between groups.ResultsCompared with the control group, the observation group demonstrated significantly shorter durations of fever, cough, and pulmonary rales, reduced antibiotic usage, and shorter hospital stays (all P < 0.001). Pulmonary function indices improved markedly (P = 0.001), and inflammatory markers showed more substantial reductions (P < 0.001). The overall treatment effectiveness in the observation group was 100%, with a caregiver satisfaction rate of 96.00% and a complication rate of 8.00%, all significantly better than those in the control group (P < 0.05).ConclusionIntegrated nursing and medical management significantly improves clinical outcomes for pediatric lobar pneumonia, accelerating recovery, enhancing pulmonary function, reducing complications, and increasing caregiver satisfaction. These findings support its broader application in clinical practice. ClinicalTrials.gov Identifierhttps://clinicaltrials.gov/study/NCT06945991, NCT06945991 (16th/April/2025).